METODE PENGOLAHAN CHICKEN MARYLAND PADA MENU A’LA CARTE WESTERN FOOD DI CRYSTAL LOTUS HOTEL YOGYAKARTA - Andriana, Maria; Widyaningsih, Heni (AKPARDA, 2023)
The purpose of this study was to determine the method of processing and serving chicken Maryland on the A’la Carte menu at Crystal Lotus Hotel Yogyakarta. This study uses a qualitative, descriptive method, with data collection techniques usingthe method of observation, literature study, and documentation. The result of this study indicate that the merhod of processing chicken Maryland at Crystal Lotus uses a deep frying process in which the fried food ingerdients must be completely submerged into the hot oil evenly so that the food can be quickly cooked into the food ingredients. Presentation of the chicken meryland menu through the stages of preparing condiments and plating chicken Maryland with mix vegetable salad, mushroom sauce, and French fries.